Personality Traits Do Not Predict How We Look at Faces. (September 2018) - Harrison, Charlotte; Binetti, Nicola; Coutrot, Antoine; Johnston, Alan; Mareschal, Isabelle
While personality has typically been considered to influence gaze behaviour, literature relating to the topic is mixed. Previously, we found no evidence of self-reported personality traits on preferred gaze duration between a participant and a person looking at them via a video. In this study, 77 of the original participants answered an in-depth follow-up survey containing a more comprehensive assessment of personality traits (Big Five Inventory) than was initially used, to check whether earlier findings were caused by the personality measure being too coarse. In addition to preferred mutual gaze duration, we also examined two other factors linked to personality traits: number of blinks and total fixation duration in the eye region of observed faces. No significant correlations were found between any of these measures and participant personality traits. We suggest that effects previously reported in the literature may stem from contextual differences or modulation of arousal.